Fundamentality and Conditionality of Existence - Rajan, Sahana (Tattva Journal of Philosophy, 2019)
In metaphysics, fundamentality is a central theme involving debates on the nature of existents, as wholes. These debates are largely object-oriented in their standpoint and engage with composites or wholes through the mereological notion of compositionality. The ontological significance of the parts overrides that of wholes since the existence and identity of the latter are dependent on that of the former. Broadly, the candidates for fundamental entities are considered to be elementary particles of modern physics (since they appear to play the role of ultimate parts to all phenomena). The paper intends to show the inadequacy of the object-oriented notion of conditionality by pointing out that the parts and wholes possess varying conditions of existence. By alleging that only the parts are ontologically significant is to conflate such conditions and neglect the spectrum of conditions which exist in our world. A proposal for a revised notion of compositionality in terms of structural relatedness is also put forward.